Effects of grafting skills and discipline on budder performance in selected orchard nursery - Rosli, Roziah (2021)
Food Industry based on the 8 Key Result Areas under the Agricultural Transformation Program indirectly became the prime mover for high demand on Jackfruit seedlings. Therefore, Department of Agriculture is responsible to produce Jackfruit seedlings. Dasar Agromakanan Negara (DAN) targeting 4630 ha landwere planted with Jackfruit on 2020. In 2019, only 2135 ha planted with Jackfruits. About 257,975 Jackfruit seedling need to produce to achieve this target. Considering that budders are different in terms of capability, expertise and crafts, more in-depth study needs to be done to address this issue. Thus, the general objective of this study is to investigate grafting skill and budder discipline in assuring successful in Jackfruit grafting. Specifically, the study was conducted to; (i) determine the level of softwood grafting skill, wedge grafting skill, budder discipline, and budder performance among nurseries, (ii) evaluate the relationship between softwood grafting skill, wedge grafting skill, discipline, and budder performance, (iii) find the most contribution factor in budder performance. The questionnaire (five sections) was prepared and arranged properly according to the demographic profiles followed by independent and dependent variables. It was design to explore the grafting procedure applied to person responsible for Jackfruit grafting (budder) through a visit of Jackfruit nurseries in Malaysia. In this research, sample of all population of 21 respondents identified and data obtained from this survey were analyzed and presented with significant statistical and test statistics. According to the study results, the level of softwood grafting skill, wedge grafting skill, budder discipline, and budder performance are same between all budders. All budders having high level of softwood grafting skill, wedge grafting skill, discipline and performance. Results from correlation show that budder discipline has very strong correlation with budder performance. The regression model output shows that budder discipline provides the highest contribution to budder performance. Budder discipline has the highest Beta value 0.742 (t=3.658, p<0.02). It shows that for every 1% increase in budder discipline (X1), budder performance (Yi) will increase by 0.716 %. This study shows that budder discipline is the dominant contributing factor for a successful production and supply of Jackfruit seedlings. The results of this study will give a real picture as well as factors that can contribute in Jackfruit seedlings production therefore, Jackfruit planting area reached as targeted.